2008
DOI: 10.1002/jcb.21878
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MicroRNA expression patterns in human fibroblasts after low‐LET radiation

Abstract: Exposure to radiation provokes cellular responses controlled in part by gene expression networks. MicroRNAs (miRNAs) are small non-coding RNAs which mostly regulate gene expression by degrading the messages or inhibiting translation. Here, we investigated changes in miRNA expression patterns after low (0.1 Gy) and high (2.0 Gy) doses of X-ray in human fibroblasts. At early (0.5 h) and late (6 and 24 h) time points, irradiation caused qualitative and quantitative differences in the down-regulation of miRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 43 publications
2
60
0
1
Order By: Relevance
“…Let-7 family of miRNAs are down-regulated except let-7g which is up-regulated in response to radiation treatment and activates cell survival pathways for radioresistance such as the Ras pathway in lung cancer cells (6). Other studies also demonstrate some miRNA targeting genes involved in radio-responsive mechanisms such as miR-521 (7), miR-579, 608, 548-3p and 585 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Let-7 family of miRNAs are down-regulated except let-7g which is up-regulated in response to radiation treatment and activates cell survival pathways for radioresistance such as the Ras pathway in lung cancer cells (6). Other studies also demonstrate some miRNA targeting genes involved in radio-responsive mechanisms such as miR-521 (7), miR-579, 608, 548-3p and 585 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic expression of miR-421 leads to S-phase cell cycle checkpoint changes and an increase in radiosensitivity [81] . Recently, more miRNAs, including miR-18a, miR-100, miR-101, miR-181, have been identified as novel regulators to control the protein level of ATM [82][83][84][85] . BRCA1, a critical tumor suppressor, is also recruited to DNA damage lesions, in which it facilitates DNA repair.…”
Section: Pan D Et Al Epigenetic Modulation and Ionizing Radiationmentioning
confidence: 99%
“…Overexpression of miR-24, the first miRNA found to target H2AX, down-regulates the level of H2AX, resulting in higher sensitivity of cells to IR [89] . Alternatively, the expression of miR-101 and miR-34a downregulated DNA-PKcs and p53 binding protein1, respectively, impeding the NHEJ repair pathway [84,90] . The tumor suppressor p53 has a central role in the activation of genes in multiple pathways, including cellcycle regulation, tumor suppression, and apoptosis.…”
Section: Pan D Et Al Epigenetic Modulation and Ionizing Radiationmentioning
confidence: 99%
“…Additional studies investigated potential biomarkers of ionising radiation exposure. Maes et al (2008) crossed microRNA, mRNA and proteomic profiling, to analyse in vitro foreskin fibroblast response to low (0.1 Gy) and high dose (2 Gy) X-rays. SAM analysis was performed.…”
Section: Using Microrna As a Biomarker Of Radiation Exposure And Radimentioning
confidence: 99%
“…In most studies, microRNA expression is inversely correlated with bioinformatically predicted target-mRNA or protein expression profile, without further validation by conventional methods, which are hard to implement because of weak post-radiation microRNA regulation. This may explain why gene ontology analysis of the identified regulated genes finds very divergent time-and dose-dependent microRNA-associated mechanisms (Maes et al, 2008). Concerning the radiation-induced bystander effect, studies reported no overall change in microRNA profile.…”
Section: Wwwintechopencommentioning
confidence: 99%